CHROMIUM ACCUMULATION IN PISTIA STRATIOTES OF USING FREE WATER SURFACE CONSTRUCTED WETLAND FOR TEXTILE WASTEWATER TREATMENT - Brilian Octavia, Putri
High production of an industry activity causes rising waste that is produced. It potentially made the pollution on environment and impacted for human health. Waste is produced by industry activity which can be contained poison and risky pollution substance (B3), such as chromium metal. Many chromium is used in a process of variety industry kinds, one of them is a textile industry. Waste water of textile industry contains a chromium with high concenteration. Chromium on heksavalen is very risky because it contents a toxic. Technology processing has an efficiency of cost, result and friendly environment for chromium waste that is contained by Constructed Wetland (CW). However, various studies are still needed to improve the effectiveness of the CW system, so that it can provide input on the determination of alternative waste treatment. This study aims to optimize the performance of the Free Water Surface type CW system and determine the efficiency of removal of pollutants in wastes with varying concentrations of chromium and organic loads, as well as assessing bioaccumulation factors in plants. In this study, two systems of CW are observed by waste-treating. They are Free Water Surface with Pistia stratiotes (FWS+Ps), and Free Water Surface without Pistia stratiotes (FWS-Ps). Pistia stratiotes is a macrophyte type of free floating. This research was carried out using artificial waste with variations in COD concentrations of 50, 100 and 150 ppm, and variations in concentrations of chromium 1,2 and 3 ppm for 10 days. The parameters analyzed were DO, pH, Turbidity, TSS, DHL, Nitrate, phosphate, COD, Chromium, and environmental quality. The results showed that the optimum efficiency of Chromium removal reached 60%, 66%, 76%, 73%, 78%, and 77%, while the optimum efficiency of COD allowance reached 79%, 72%, 75%, 66% respectively. , 88%, and 94% in variations 1,2 / 50, 3/50, 1,2 / 100, 3/100, 1,2 / 150, and 3/150. The accumulated value of chromium is greater in the root part compared to shoot. The model that can be used in determining the relationship between polluting compounds and decreasing the concentration of nutrients represented as nitrate and phosphate in the Constructed Wetland type of Free Water Surface using Pistia stratiotes are: COD = -0,066 x + 0,107 y + 61,419 and Chrome = -0,030 x + 0.099 y +47,255.